A neurocognitive framework of attention and creativity: Maximizing usefulness and novelty via directed and undirected pathways - Yeo, G.B.; Celestine, N.A.; Parker, Sharon K.; To, M.L.; Hirst, G. (2024)
Coming up with creative ideas is not easy. In this conceptual article, we integrate organizational behavior, cognitive psychology, and neuroscience literatures to propose that different forms of attention may be a key to maximizing creative usefulness and novelty. Specifically, we develop a neurocognitive framework of attentional control to propose differential pathways from creative goal-directed attention (a narrow and selective focus) to deliberate information processing, and from undirected attention (a wide and unconstrained focus) to spontaneous information processing. These propositions have implications for creative usefulness and novelty, respectively—namely, that creative goal-directed attention should facilitate the usefulness of creative outputs to a greater extent than their novelty, whereas undirected attention should promote the novelty of creative outputs to a greater extent than their usefulness. Our framework further suggests that time spent experiencing creative goal-directed attention followed by undirected attention is the optimal sequence for maximizing both the usefulness and novelty of creative outputs. In combination, our framework advances theoretical understanding of attentional pathways to creative outcomes and offers practical implications for maximizing creative potential at work.